2022
DOI: 10.1016/j.ebiom.2022.103838
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics counteract hepatic steatosis caused by ketogenic diet and upregulate AMPK signaling in a model of infantile epilepsy

Abstract: Background Infantile spasms syndrome (IS) is a type of epilepsy affecting 1.6 to 4.5 per 10,000 children in the first year of life, often with severe lifelong neurodevelopmental consequences. Only two first-line pharmacological treatments currently exist for IS and many children are refractory to these therapies. In such cases, children are treated with the ketogenic diet (KD). While effective in reducing seizures, the diet can result in dyslipidemia over time.Methods Employing a neonatal Sprague-Dawley rat mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…From the present data, we are unable to discern whether changes in cytokines were a cause or were a result of reduced spasms. However, based on the ability of selected probiotics to suppress chronic inflammation and oxidative damage (21,36), we suspect that the administered probiotics may ameliorate inflammatory responses, contributing to the observed anticonvulsant effects. JCI Insight 2022;7(12):e158521 https://doi.org/10.1172/jci.insight.158521…”
Section: Discussionmentioning
confidence: 99%
“…From the present data, we are unable to discern whether changes in cytokines were a cause or were a result of reduced spasms. However, based on the ability of selected probiotics to suppress chronic inflammation and oxidative damage (21,36), we suspect that the administered probiotics may ameliorate inflammatory responses, contributing to the observed anticonvulsant effects. JCI Insight 2022;7(12):e158521 https://doi.org/10.1172/jci.insight.158521…”
Section: Discussionmentioning
confidence: 99%
“…Data regarding the impact of normal carbohydrate and the KD on spasms, metabolites, and the gut microbiota have been previously published [ 3 , 8 , 26 ]. Both male and female animals were used for the study.…”
Section: Methodsmentioning
confidence: 99%
“…Employing antibiotics and fecal microbiota transfer into germ-free mice, Olson and colleagues [ 7 ] demonstrated that the seizure-reducing effects of the diet are dependent on the gut microbiota in two rodent models of epilepsy. Likewise, gut-microbiome-based manipulations, including the KD, antibiotics, and probiotics, have been shown to suppress seizures (spasms) in a neonatal brain injury rat model of infantile spasms [ 3 , 8 , 9 ]. Similar to the abovementioned study, the protective impacts of the diet could also be transferred to another animal by fecal transplant alone, showing the gut-based dependency of the treatment [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The companion piece by Mu et al. 3 leans further to the clinical side and in doing so provides a striking finding of potential immediate use. When employed in infantile spasms syndrome (as a common recourse in the case that pharmacological approaches fail), 5 the ketogenic diet can damage the developing and under-protected liver.…”
mentioning
confidence: 97%
“… 1 Recently, tantalising discoveries have suggested that such modifications could target the gut microbiome, an apparent key player in the causal chain leading from the ketogenic diet to anti-seizure changes in the brain. 2 Two research papers by Mu and colleagues published recently in eBioMedicine 3 , 4 make valuable progress in the direction of ketogenic diet optimization, in the specific case of infantile spasms syndrome. Their findings are particularly noteworthy for their direct clinical implications, but also advance our understanding of particular mechanisms of the ketogenic diet in infantile spasms.…”
mentioning
confidence: 99%